The Implementation of Academic Supervision by The Principal to Improve Teacher Performance at State Elementary School 07 Purwoharjo, Comal District, Pemalang Regency - Jalu Ferari Septiarso; Widya Kusumaningsih; Qristin Violinda (Journal of Educational Sciences, 2026)
Teacher performance is one of the key factors in determining the quality of learning processes and outcomes in elementary schools. Therefore, academic supervision by the principal should be conducted in a planned and sustained manner to improve teachers’ competencies and performance. This study aims to describe the implementation of academic supervision by the principal in improving teacher performance at SD Negeri 07 Purwoharjo. The study employed a qualitative approach with a case study design. The research subjects consisted of the principal and teachers. Data were collected through observation, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis followed the model developed by Matthew B. Miles and A. Michael Huberman. The results show that academic supervision is conducted through planning, implementation, evaluation, and follow-up stages. Planning involves reviewing educational reports, previous supervision results, and teachers’ needs. Implementation includes guidance, mentoring, classroom observation, and the use of the e-performance application. Evaluation involves feedback, documentation, and reflection on learning. Follow-up includes personal coaching, discussions, learning communities, teacher working groups (KKG), training, and periodic monitoring. Personal coaching and ongoing mentoring were the most prominent follow-up measures because they encouraged teachers to reflect, identify challenges, and develop improvement plans independently.